Are severe forms of thyroid eye disease common in the indian population? Clinical characteristics of 136 patients from a tertiary eye care centre - Dhakshini L Subramaniam; Dayakar Yadalla; Jayagayathri Rajagopalan (Indian Journal of Endocrinology and Metabolism, 2023)
Context: Considerable evidence of gender, ethnicity, thyroid dysfunction, and environmental factors including smoking influencing the development and progression of thyroid eye disease (TED). Settings and Design: Cross-sectional study of the clinical characteristics of 136 patients with TED who presented to the Orbit and Oculoplasty services at a tertiary eye care center in south India between October 2018 and June 2020. Results: Among the 136 patients (M: 61, F: 75), the mean age was 47.04 (SD ± 13.24) years. Hyperthyroid disease was present in 53%, hypothyroid disease in 40%, and 7.3% were euthyroid. Active disease was noted in 25% and inactive disease in 75% of patients. Active disease was present in 25% of hyperthyroid, 18.5% of hypothyroid, and 15% of euthyroid patients. Active TED showed statistically significant association toward development of greater severity of proptosis (P = 0.001), optic neuropathy (P = 0.004), and extraocular movement restriction (P < 0.001) as compared to inactive disease. Mild, moderate to severe, and sight-threatening TED was noted in 34.6%, 59.6%, and 6% of patients, respectively. Nine eyes had dysthyroid optic neuropathy, of which eight had either mild or no proptosis while one had moderate to severe proptosis. Conclusion: Prevalence of active as well as severe thyroid eye disease is common in our population. Recommendation for ophthalmological examination of patients even with milder disease especially when associated with decreased vision and signs of inflammation. Active disease is less common in euthyroid patients, thus necessitating maintaining the euthyroid status toward reducing disease activity and progression.